Epidemiology of primary Sjogren’s syndrome: a systematic review and meta-analysis - Qin, B.; Wang, J.; Yang, Z.; Yang, M.; Ma, N.; Huang, F.; Zhong, R. (Ann Rheum Dis, 2015)
OBJECTIVE: Epidemiological studies of primary Sjogren’s syndrome (pSS) are crucial for describing the burden to society and the public medical system and for shedding light on aetiology. Previous reports of the epidemiology of pSS show variable outcomes. We conducted a systematic review of the epidemiology of pSS to assess the prevalence rates (PRs) and incidence rates (IRs), and to investigate possible geographic variations in pSS. METHODS: A systematic literature search of PubMed and Embase (updated to 22 October 2013) was performed to identify all published reports on the epidemiology of pSS. The incidence and prevalence rates of pSS were summarised with IRs or PRs and 95% CIs. RESULTS: The literature search yielded 1880 related citations. Only 21 fulfilled the inclusion criteria. According to a random-effects model, the pooled IR for pSS was 6.92 (95% CI 4.98 to 8.86) per 100 000 person-years. The overall PR was 60.82 (95% CI 43.69 to 77.94) cases per 100 000 inhabitants with a slightly lower estimate of Baodong Qin is BDQ, Jiaqi Wang is JQW, Zaixing Yang is ZXY, Renqian Zhong is RQZ. 43.03 (25.74 to 60.31) cases per 100 000 inhabitants when only considering population-based studies. The female/male ratio in incidence data was 9.15 (95% CI 3.35 to 13.18). The female/male ratio in prevalence data was 10.72 (95% CI 7.35 to 15.62). The overall age of pSS patients was 56.16 years (95% CI 52.54 to 59.78). CONCLUSIONS: Incidence and prevalence rates of pSS vary widely around the world. The results help us better understand the global epidemiology of pSS. Large population-based studies combining meticulous case-finding and case-ascertainment strategies are needed.